Analysis of cortical bone porosity using synchrotron radiation microtomography to evaluate the effects of chemotherapy. (November 2015) - Alessio, R.; Nogueira, L.P.; Salata, C.; Mantuano, A.; Almeida, A.P.; Braz, D.; de Almeida, C.E.; Tromba, G.; Barroso, R.C.
Abstract: Microporosities play important biologic and mechanical roles on health. One of the side effects caused by some chemotherapy drugs is the induction of amenorrhea, temporary or not, in premenopausal women, with a consequent decrease in estrogen production, which can lead to cortical bone changes. In the present work, the femur diaphysis of rats treated with chemotherapy drugs were evaluated by 3D morphometric parameters using synchrotron radiation microtomography. Control animals were also evaluated for comparison. The 3D tomographic images were obtained at the SYRMEP (SYnchrotron Radiation for MEdical Physics) beamline at the ELETTRA Synchrotron Laboratory in Trieste, Italy. Results showed significant differences in morphometric parameters measured from the 3D images of femur diaphysis of rats. Highlights: Changes in cortical bone porosity due to chemotherapeutic drugs. 3D morphometric parameters with synchrotron radiation microtomography. Chemotherapy induced bone loss in rats.